2023
DOI: 10.3390/ani13162633
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of the Gastrointestinal Tract of Chicks with Different Bacterial Microbiota Profiles

Abstract: This study aimed to investigate the consequences of early-life microbiota transplantation using different caecal content sources in broiler chicks. We hypothesized that chicks receiving at-hatch microbiota from organic hens would harbour a distinct microbiota from chicks receiving industry-raised broiler microbiota after six weeks of age. Three hundred Cobb broilers eggs were randomly assigned to one of four groups according to the caecal content received: organic laying hens (Organic); autoclaved caecal conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…The effects of early-life CMT on the development of the gut microbiota in recipient chickens with long-lasting effects have been previously investigated. Franco et al reported that broiler chicks (recipients) that received cecal contents from organic hens or industry-raised broilers (donors) by oral application on day 1 had distinctly colonized bacterial microbiota profiles, which was similar to the cecal microbiota profiles of the donors, respectively [ 212 ]. The differences between the recipient broilers had been maintained from day 7 to day 42 (the end of this study).…”
Section: Cecal Microbiota Transplantation Social Stress and Injurious...mentioning
confidence: 99%
“…The effects of early-life CMT on the development of the gut microbiota in recipient chickens with long-lasting effects have been previously investigated. Franco et al reported that broiler chicks (recipients) that received cecal contents from organic hens or industry-raised broilers (donors) by oral application on day 1 had distinctly colonized bacterial microbiota profiles, which was similar to the cecal microbiota profiles of the donors, respectively [ 212 ]. The differences between the recipient broilers had been maintained from day 7 to day 42 (the end of this study).…”
Section: Cecal Microbiota Transplantation Social Stress and Injurious...mentioning
confidence: 99%